Malaysia Festival (MAFES) - culture restored / Zarifah Mohd Zain - Mohd Zain, Zarifah (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2019)
Culture signifies the identity of the nation in a country. As a multi-racial country, Malaysia houses various types of cultural heritage from our three main ethnics which are Malay, Chinese and Indian as well as other ethnics and tribes like Baba Nyonya, Kristang, Jawi Peranakan, Kadazan, Murut, Bidayuh and many others. However, due to the changes in time and technological advancement, the knowledge and practices of our cultural heritage are deteriorating. People especially the youngsters do not appreciate the philosophies and practices of their own cultures. Realizing the possibility that the precious cultural heritage of Malaysians might be extinct if it is not well-preserved, the third semester students of Diploma in Tourism Management (HM1111) had organized Malaysia Festival (MAFES) - Culture Restored.